Redes inalámbricas 802.11 y su incidencia en el aprendizaje movil (m-learning) de los estudiantes de la Facultad de Ciencias Jurídicas, Sociales y de la Educación de la Universidad Técnica de Babahoyo - Navarrete Valencia, Gissella Sulay (2018)
In the present investigation the respective study can be developed on the knowledge obtained by the personal experience, the observation or the study and the transmission of this knowledge has been given by means of the education. For millions of years, knowledge has helped man to create technology and take better advantage of existing resources. These advances in technology have taken us to the world in which we live today. The new educational challenges that arise today, it is clear that digital literacy in education is necessary to be able to face these challenges. The use of virtual platforms will allow better communication and feedback between teachers and students, a flaw that is seen in the application of current traditional classes. Young people use social networks, however, they rarely consult about class or research issues. For there to be communication between two stations, both have to be connected to the same access point and do not have to be directly between them. When a client wants to send a message to another station, it sends it to the access point, and the latter forwards it to the destination station; that is, it is a completely centralized system. The fall of the wireless access point causes the total disconnection of the network. From here we can also deduce that the area of local coverage is equivalent to the area of coverage that has the access point, which can range from thirty meters to hundreds in the best possible conditions